THE ISOLATION SINGLE ET1, ET2, ET3 MUTANTS AND GENERATION DOUBLE ET1/ET2 MUTANTS OF THE ET GENE FAMILY IN Arabidopsis Thaliana - Thi Mai Huong, Bui; Bäumlein, Helmut (Journal of Forestry Science and Technology, 2020)
EFFECTORS OF TRANSCRIPTION (ET) are plant-specific regulatory proteins characterized by highly conserved ET repeats. These proteins are involved in zinc and DNA binding. Therefore, It was supposed that ETs might act as epigenetic regulators. Isolation single mutant alleles et1, et2, et3 and generation double et1/et2 mutants have been proposed as a powerful tool for identifying, confirming the function of ET family. Here, we describe the structural characterization of the three member Arabidopsis thaliana ET gene family. Then, Identifying a mutation in the genes of interest by PCR screening of pools of insertion lines, using one primer corresponding to interest genes and one primer corresponding to the end of the insertion element (T-DNA). The two double mutants have been generated by crossing the homozygous mutant et1-1 both with homozygous et2-1 and et2-3 mutants. The homozygous double mutants et1-1 et2-1 and et1-1 et2-3 have been selected and characterized in the F2 generation. In this study we got two et1 lines : homozygous et1-1 with the T-DNA insertion is positioned in the second exon and heterozygous et1-5 with the T-DNA insertion in et1-5 is now located far up in the 5`flanking region, 699 bp in front of the translation start; Two et2 lines : homozygous et2-1 with T-DNA insertion are positioned in the second exon and homozygous et2-3 with T-DNA insertion are positioned in first exon; Two et3 lines : heterozygous et3-2 and heterozygous et3-3 with T-DNA insertion are located at promoter 239bp and 216bp in front of the translation start, respectively. And we have been generated two lines double mutants et1/et2: homozygous et1-1/et2-1 and homozygous et1-1/et2-3.